2008
DOI: 10.1002/lt.21373
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde oxygen persufflation preservation of human livers: A pilot study

Abstract: Retrograde oxygen persufflation as a supplement of cold storage during the preservation period has the potential to better utilize ischemically damaged marginal livers in the experimental setting. Retrograde oxygen persufflation was applied in selected livers to demonstrate feasibility in the clinical setting and to investigate potential beneficial effects. Between 4/04 and 3/05 5 marginal otherwise discarded livers with warm ischemic damages from deceased donors (age 52 ) were accepted for transplantation. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…For kidney preservation, VSOP was first described by Talbert et al [15] in 1961, and has since then demonstrated the capability of extending the allowable warm and cold ischemia times as well as better maintenance of organ viability when compared to CS and MP [8,11,16]. In the past decades, the feasibility of the clinical application of VSOP was demonstrated in a kidney and a liver preservation feasibility study [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…For kidney preservation, VSOP was first described by Talbert et al [15] in 1961, and has since then demonstrated the capability of extending the allowable warm and cold ischemia times as well as better maintenance of organ viability when compared to CS and MP [8,11,16]. In the past decades, the feasibility of the clinical application of VSOP was demonstrated in a kidney and a liver preservation feasibility study [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies (2,3); VSOP reduced apoptosis; and improved graft viability by increasing tissue adenosine triphosphate (ATP) concentration, vascular endothelial function and ultrastructure in several models. In a clinical pilot study for deceased-DLT, Treckmann et al (14) reported that the VSOP during cold storage increased ATP more than twofold and, thus, improved early aerobic metabolism; therefore, the VSOP could potentially improve primary organ function after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Liver grafts underwent R-PSF at 18 mmHg at least one hour before transplantation. Evaluation of the histological biopsies taken before and after R-PSF showed that ATP level was enhanced by 2-5 times after R-PSF treatment, and all the patients survived during the two years of observation period with good graft function panel [16] .…”
Section: Oxygenated Cold Storage (Persufflation)mentioning
confidence: 92%
“…They first established the model on rodent liver and continued with large animals (pig) and were able to demonstrate the benefits of PSF by improving the quality of liver grafts [15] . They also showed the feasibility of this method by publishing the outcome of five patients transplanted with persufflated livers [16] . The livers underwent WIT between 20-60 min and they were rejected by all the other transplant centers for transplant.…”
Section: Oxygenated Cold Storage (Persufflation)mentioning
confidence: 99%